Transgender In Achieving The Social Acceptability In Pematangsiantar - Donny Paskah Martianus Siburian; Harmona Daulay; Junjungan SBP Simanjuntak; Rizabuana Ismail; Hadriana Marhaeni Munthe (Universitas Trunodjoyo Madura, 2023)
Society expects men to behave in a masculine manner and fulfill traditional male roles, while women are expected to behave in a feminine manner and exhibit normal heterosexual behavior, such as engaging in sexual relations with the opposite sex. The existence of transgender individuals in society is often perceived as deviant. The purpose of this research is to examine the community's stereotypes towards transgender individuals in Pematangsiantar City and the adaptation strategies implemented by transgender individuals who are accepted in society. This research employs a mixed-method approach, with a focus on qualitative data analysis supplemented by quantitative data. The results of this study indicate that various negative stereotypes are associated with transgender individuals in Pematangsiantar City. Consequently, transgender individuals must use various strategies and make efforts to adapt and be accepted as themselves and as members of society. This research can serve as a reference for addressing social life and social status as a transgender individual amidst society.